(untitled) (Journal of Fatima Jinnah Medical University, 2025)
Background: Post-partum hemorrhage (PPH) is known in to occur in more than 10% of cesarean sections. Generally intravenous or intramuscular oxytocin is commonly used for prevention of PPH, nevertheless, in some studies rectally administered misoprostol has been shown to be superior to oxytocin in this regard. This route is also linked with fewer side effects and longer half-life. This study was designed to compare the outcome of per rectal misoprostol versus I.M oxytocin in the prevention of post-partum hemorrhage in cesarean section. Patients and methods: A randomized controlled trial was conducted at the Department of Obstetrics and Gynaecology, Sir Ganga Ram Hospital, Lahore from 1st November 2021 to 30th April 2022. Women undergoing cesarean section were either given 10 IU of injection oxytocin intramuscularly or 800 micrograms Misoprostol per rectally in addition to IV oxytocin infusion in all patients. Difference in hemoglobin levels before and after the cesarean section were compared. Pre-designed data collection performa were used for data collection and the data were analyzed using SPSS version 25.0. Results: A total of 88 patients were randomized in to two groups of 44 patients each. The mean age of participants in misoprostol group was 30 ± 4 years and in oxytocin group was 29 ± 5 years. The most common indications for cesarean sections were fetal distress due to multiparity, which was present in 33 (37.5%) cases, followed by prolonged labor in 22 (25%), polyhydramnios with fetal malpresentation in 20 (22.7%), and multiple gestation with malpresentation of first fetus in 13 (14.5%) cases. The mean change in hemoglobin was lower in the misoprostol group (0.7 ± 0.26 g/dL) than the oxytocin group (1.17 ± 0.45 g/dL) and the results showed statistical significance (p = 0.000). Conclusion: Rectally administered misoprostol is superior to intramuscular oxytocin in the prevention of post-partum hemorrhage and can be used as an alternative in patients undergoing cesarean section.